Cultivation systems and planting seasons effects on the vegetative growing of net melon cultivars - Pádua, J. G.; Braz, L. T. [UNESP]; Banzatto, D. A. [UNESP]; Gusmão, M. T A [UNESP]; Gusmão, S. A L (My University, 2003)
Growth effects of cultivation on soil, sand and commercial substrate, on summer and winter time, of 'Bonus #2', 'Don Carlo's and 'Hy Mark' were assessed. The experiments were conducted in a greenhouse of FCAV-UNESP, in Jaboticabal- SP, Brazil, 21° 15' 22 S, 48° 18'58 W, and an altitude of 595 m, comprising the period from November '99 to April 2000 (Summer), and from July to November 2000 (Winter). On soil cultivation, chemical nutrients were used, and the plants received drip irrigation. On sand, fertigation with recirculation of the nutrient solution were used, and slabs and fertigation with non circulating nutrient solution was used with commercial substrate. 'Bonus #2', grown on sand and in the summer season had improved plant height, internodes length, stem diameter, leaf area and dry matter of shoots and roots. 'Hy Mark', when cultivated on commercial substrate had lower growth. During winter season, the growth was slower.
Keywords: Cucumis melo; Hydroponic systems; Plant growth; Soilless culture; Substrates